Meningkatkan Potensi Wisata Di Pantai Ujung Batu Padang - Nidia Wulansari; Arif Adrian; Dadra Are Putra; Rizky Wulandari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Ujung Batu Beach has the potential to become a tourist destination. This potential, however, has not been completely realized. This community service project is intended to assist managers and the community in identifying existing potential. Location determination, work program determination, work program realization, and work program evaluation are the approaches used. This dedication has resulted in the production of supporting facilities such as signage, swings, flower pots, and garden seats. Furthermore, socialization was provided to the community so that it might play an active role in boosting tourist attraction.